Study of sparse frequency waveform for modern radar applications - Mou, Boxin (2015)
Radio frequency interference (RFI) is the key concern for modern radar design and signal transmission, especially as electronic warfare (EW) has been of key concern for many countries in modern air combat. With one or more interference signals in the desired signal band, the transmitted signal cannot be fully recovered by the receiver, as a result of which the positioning and speed detection functions of radar could not be performed. This report addresses RFI suppression using the sparse waveform design and frequency notching. The performances of utilizing both techniques are evaluated using MATLAB simulation. The sparse waveform design that is investigated in the paper is the Spectrally Shaped Waveform Design recently proposed. With the results obtained from simulations, it is discovered that the sparse bands transmission and reception method has a better performance in terms of the SINR improvement but the wideband transmission and sparse bands reception method is better in terms of the sidelobe level suppression. It is therefore important to evaluate the focus of the transmission when choosing between the two methods. Further investigation on the optimization on the design of the two methods could be carried out in future work to improve sidelobe level suppression and SNR improvement in signal transmission and reception.